Trente années d'observation des micro-algues et des toxines d'algues sur le littoral - Belin, Catherine (éditions Quae, 2018)
Rephy and Rephytox are coastal monitoring networks created by Ifremer. Their purpose is to observe the phytoplankton and associate hydrological parameters and to detect the algal toxins accumulating in shellfish. This work describes these networks before providing a global vision of data acquired during the last three decades. It shows the importance of series of environmental data acquired in the long term.rticulier aux scientifiques travaillant sur les écosystèmes littoraux, maisaussi à tout public intéressé par ces problématiques.